Explorations about the Conceptualizations and Practices about the Body and the Non- verbal Communication: The School, the Learning Process and the Foreign Language Classroom - Quiñones, Jesus Antonio (2020)
This study describes how to address nonverbal communication in EFL classrooms and how it may be related to concepts and practices regarding the body within the context of an all-girls school in Bogotá, Colombia. The subjects of the study are  42 tenth-grade female students ranging from 14 to 17 years of age, who were experiencing difficulty and fear in using nonverbal communication in their foreign language class. This is a qualitative study that was conducted in various phases based on a descriptive case study that involved: design of thought-provoking questions, data collection, data analysis and interpretation, and findings. The methodology was based on observation, questionnaires and semi-structured interviews. Results reveal that, at school, the human body is configured according to physical, biological and moral perspectives. At the same time, students state that they do not consider the body relevant to learning. This reflects an overall lack of knowledge about the experiential, communicative, symbolic and cultural dimensions of the body. This study emphasizes the importance of the body within a school context that should be included as part of an interdisciplinary process to support the construction of subjectivity and the possibility of interacting with one´s otherness which, in this case, is understood as the particularities of a foreign culture.